Determinants of sovereign yield spreads during the Euro-crisis: Fundamental factors versus systemic risk - Jens Klose; Benjamin Weigert (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2012)
The intensity of the Euro-crisis was reflected by significant increases of sovereign bond yields in the troubled countries. This has launched a hot debate whether this increase can solely be attributed to fundamental factors like e.g. rescue programmes, rising budget deficits, deteriorating economic prospects or changes in the rating-status of the country, or whether a part of these growing yields is likely to represent a systemic risk, i.e. that one or more countries will drop out of the European Monetary Union and reintroduce their own national currencies. This empirical analysis explores whether such systemic risk is present in the yield spreads of nine Euro area countries by using a novel market based indicator from the virtual prediction market Intrade. Our empirical results suggest that beside fundamental factors a systemic risk component played a role in determination of sovereign yields. Our empirical measure of the systemic component in sovereign yields can be related to the expected change of the newly introduced national currency. Accordingly to that, Portugal, Ireland, Spain and Italy are expected to depreciate their currency while the others would appreciate after a withdrawal from the Euro area. Risk premia that are related to fears of the reversibility of the Euro are unacceptable, and they need to be addressed in a fundamental manner. (ECB-President Mario Draghi, August 2012) Es gibt fundamentale Zweifel der Märkte an der Sicherheit der Währungsunion. (Bundesbankpräsident Jens Weidmann, July 2012)
More recent version: http://hdl.handle.net/10419/92397
Keywords: 330